Trial of Dexmethylphenidate (Focalin) ER in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The efficacy and safety of dexmethylphenidate extended release (d-MPH-ER) was compared to placebo in 97 patients (ages 6-17 years) with attention-deficit/hyperactivity disorder (ADHD) in a multicenter, randomized, double-blind, two-phase study reported from New York State Psychiatric Institute, New York.